Pengaruh Profesionalisme Auditor Terhadap Pertimbangan Tingkat Materialitas Dalam Proses Pengauditan Laporan Keuangan (Studi Empiris Pada Auditor KAP Di Surakarta Dan Yogyakarta) - Fitriyani, Deni Nofita, Drs. Wahyono, MA. Ak (2015)
This research objective is to examine empirically the influence of professionalism of auditor on level of materiality in course of financial statement audit. Professionalism of auditor which estimate can influence level of materiality is devotion of at profession, social obligation, independence, belief of at profession, and relation with humanity of friend profession. Data is selected using convinience sampling. The analysis units for responses of 35 staff in KAP Surakarta and Yogyakarta. The data collection is performed using questioner. The statistic method used to test the hypotheses is multiple regressions. The study results are as follows: 1) the influence of devotion of at profession on materiality. Result of researches has done Rahmawati (1997) and Hastuti et al. (2003), 2) the influence of independence on materiality. Result of researches has done Rahmawati (1997) and Hastuti et al. (2003), 3) the influence of belief profession on materiality Result of researches has done Rahmawati (1997) and Hastuti et al. (2003), 4) the influence of relation with humanity of friend profession. Result of researches has done Rahmawati (1997) and Hastuti et al. (2003), also 5) the influence of devotion of social obey on materiality do not support research of Rahmawati (1997) and Hastuti et al. (2003). This research also indicate that by using five dimension of professionalism that is: devotion of at profession, social obligation, independence, belief of at profession, and relation of humanity of friend of profession can influence a auditor in considering storey level materiality. Consideration mount materiality influenced by the professionalism, consistence with result of previous research.